2021
DOI: 10.1108/jima-06-2020-0184
|View full text |Cite
|
Sign up to set email alerts
|

Celebrity transgression and consumers’ forgiveness: does religiosity matter?

Abstract: Purpose This paper aims to examine the role of religiosity on consumers’ forgiveness when celebrities get involved in transgression. The celebrity’s reaction and its impact on consumers’ forgiveness is tested as well. In addition, consumers’ attitudes towards the brand and celebrity as well as purchase intention for the endorsed brand are examined both before and after the transgression. Design/methodology/approach Data (n = 356) were collected through a self-administered online survey and analysed though st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 84 publications
1
3
0
2
Order By: Relevance
“…It is therefore expected that the purchasing behaviour of Muslim consumers might be accordingly affected towards halal products (Garg and Joshi, 2018). This is congruent with many studies which reported that individuals following religious teachings exhibited higher tendencies towards positive behaviour compared to individuals with fewer religious practices (Shimul et al , 2021). Thus, the religiosity factor could moderate the relationship between attitude and the continuance of use of non-halal certified cosmetics.…”
Section: Introductionsupporting
confidence: 91%
“…It is therefore expected that the purchasing behaviour of Muslim consumers might be accordingly affected towards halal products (Garg and Joshi, 2018). This is congruent with many studies which reported that individuals following religious teachings exhibited higher tendencies towards positive behaviour compared to individuals with fewer religious practices (Shimul et al , 2021). Thus, the religiosity factor could moderate the relationship between attitude and the continuance of use of non-halal certified cosmetics.…”
Section: Introductionsupporting
confidence: 91%
“…Celebrity endorsers’ credibility has positive impacts on consumer’s recognition of them and of the products they endorse ( Pornpitakpan, 2008 ). Once a celebrity commits a transgression, consumer attitudes toward that celebrity become weaker ( Shimul et al, 2020 ). Unethical behaviors exert a negative influence on both the celebrity and the brands they are endorsing ( Thomas and Fowler, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…There are many studies about social responsibility, but these tend to concentrate on the social responsibility of enterprises, not of individuals ( Zhong, 2018 ; Shimul et al, 2020 ). Some related research has noted celebrity misconduct, such as advertising endorsements, drug abuse, and divorce, but few studies have defined the concept of (individual) celebrity social responsibility.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Berdasarkan informasi ini, persaingan dalam industri perawatan kulit semakin ketat, dan perusahaan perlu mengembangkan strategi pemasaran yang efektif untuk meningkatkan minat pembelian konsumen. Penelitian oleh Shimul & Barber (2020) menunjukkan bahwa sikap positif konsumen terhadap selebriti endorser dapat meningkatkan minat pembelian produk. Selain sikap terhadap selebriti, daya tarik selebriti juga memainkan peran penting dalam memengaruhi minat pembelian.…”
Section: Pendahuluanunclassified